Using Case-Based Learning to Teach Information Literacy and Critical Thinking Skills in Undergraduate Music Therapy Education: A Cohort Study. Issue 2 (7th January 2020) - Masko, Meganne K; Thormodson, Kelly; Borysewicz, Kristen
Abstract: Higher education traditionally focuses on didactic, or passive, teaching and learning techniques as these are efficient ways of conveying information to the students. However, passive learning places the responsibility for students' learning on the instructor rather than the students themselves. Constructive learning techniques, such as case-based learning (CBL), give students opportunities to apply previous knowledge while constructing their own deep learning. The purpose of this article is to describe both the implementation and evaluation of a CBL unit in a junior-level undergraduate music therapy theories and methods course. The cohort study utilized student reflection papers, faculty observations, class materials, and a student survey to evaluate the impact of a behavioral health-focused CBL unit on information literacy, critical thinking skills, and student enjoyment of learning. Students answered both Likert-type and open-ended questions on these topics. Open-ended questions were analyzed using a directed qualitative content analysis. Students felt that the CBL unit was effective in increasing their information literacy and critical thinking skills, and they enjoyed the unit. According to survey results, the CBL developed several measured areas of student critical thinking skills, with the exception of the students' abilities to analyze their own biases. The CBL unit appeared to be an effective and efficient way of simultaneously covering multiple learning outcomes and music therapy competencies. However, students did not perceive any changes in their ability to analyze their own biases which, based on previous psychology and sociology research, takes more than one isolated learning unit to address. Implications for music therapy education are addressed.